Electrodeposition of Protocrystalline Germanium from Supercritical Difluoromethane. Issue 5 (2nd March 2016) - Cummings, Charles Y.; Bartlett, Philip N.; Pugh, David; Reid, Gillian; Levason, William; Hasan, Mahboba M.; Hector, Andrew L.; Spencer, Joe; Smith, David C.; Marks, Samuel; Beanland, Richard
Abstract: We report results for the electrochemistry of the germanium(II) tri‐halide anions, [GeCl3 ] −, [GeBr3 ] − and [GeI3 ] −, in supercritical difluoromethane containing 60 mm [N n Bu4 ][BF4 ] at 19.1 MPa and 358 K. The voltammetry shows mass‐transport‐limited currents for reduction to germanium at gold on the first scan. There is no evidence of a germanium stripping peak and, on subsequent scans, the electrode slowly passivates with the deposition of approximately 0.4 μm of material. The redox potentials for the reduction of the three tri‐halides are in the order [GeCl3 ] − <[GeBr3 ] − <[GeI3 ] −, with the iodide being the most easily reduced complex. Electrodeposition of germanium onto TiN electrodes from supercritical difluoromethane at 19.1 MPa and 358 K, using either 16 mm [EMIM][GeI3 ] with 60 mm [EMIM][BF4 ] or 16 mm [N n Bu4 ][GeI3 ] with 60 mm [N n Bu4 ][BF4 ], gave deposition rates of 2–3 μm h −1 . Raman spectroscopy and transmission electron microscopy showed that the resulting germanium films were protocrystalline, containing nanocrystals of germanium embedded in an amorphous germanium matrix. Abstract : Ge whizz : Of the three germanium(II) tri‐halide anions, [GeCl3 ] −, [GeBr3 ] − and [GeI3 ] −, the iodide species is the most easily reduced in supercritical CH2 F2 and can be used to deposit amorphous films containing embedded Ge nanocrystals.